2008
DOI: 10.14411/eje.2008.115
|View full text |Cite
|
Sign up to set email alerts
|

Host ant specificity of large blue butterflies Phengaris (Maculinea) (Lepidoptera: Lycaenidae) inhabiting humid grasslands in East-central Europe

Abstract: Abstract. Butterflies of the genus Phengaris have a highly specialised life cycle involving an obligatory relationship with Myrmica ants. A knowledge of the host ant specificity is essential for understanding the relationship between a particular Phengaris species and its hosts and also important for the conservation of these butterflies. Data on host ant specificity were collected in Poland, the Czech Republic, Slovakia and Ukraine. Five different Myrmica species were used by P. teleius as hosts (M. scabrinod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 33 publications
6
51
0
3
Order By: Relevance
“…In Poland, Woyciechowski and Miszta (1976) and Petal (1974Petal ( , 1980 found 4-14 ant species on the moist meadows where the source populations of the reintroduced butterflies occur. On such meadows, M. scabrinodis usually dominates the ant community (Grill et al 2008;Witek et al 2008), which agrees with our findings. On road verges, however, L. niger is by far the commonest species.…”
Section: Discussionsupporting
confidence: 93%
“…In Poland, Woyciechowski and Miszta (1976) and Petal (1974Petal ( , 1980 found 4-14 ant species on the moist meadows where the source populations of the reintroduced butterflies occur. On such meadows, M. scabrinodis usually dominates the ant community (Grill et al 2008;Witek et al 2008), which agrees with our findings. On road verges, however, L. niger is by far the commonest species.…”
Section: Discussionsupporting
confidence: 93%
“…Further studies are required to resolve the detailed mechanism of the negative effect of goldenrod on particular species. All observed Myrmica species are host ants of Phengaris butterflies (Witek et al 2008). In the context of previous studies showing significant correlations between local extinctions of hosts and parasites (Koh et al 2004), Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2 The average (±SD) number of species (a); number of nests (b) and ratio of the number of L. niger nests in the total nest number of Myrmica and Lasius species (c) in control (white bars) and goldenrod (gray bars) squares goldenrods may also have a negative effect on these flagship species. In the context of extreme local specificity of P. alcon for M. scabrinodis ants (Sielezniew and Stankiewicz 2002) as well as the high specificity of P. nausithous for M. rubra, goldenrod invasion potentially threatens these two butterfly species to a higher degree than the more flexible P. teleius which does not show local specialization to host ants Witek et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been carried out on host ant specificity between Maculinea butterflies and their Myrmica host ants in recent years. Most of them are based on recorded frequency distribution of Maculinea pupae in relation to the host ant species they were found with (Elmes et al, 1994Stankiewicz and Sielezniew, 2002;Als et al, 2004;Tartally and Cs} osz, 2004;Woyciechowski et al, 2006;Tartally and Varga, 2008;Witek et al, 2008, Patricelli et al, 2010. A more mechanistic understanding of host specificity in Maculinea-Myrmica association has been achieved by studying chemical and acoustic mimicry Barbero et al, 2009) and through the investigation of ant adoption and rearing behaviour (Als et al, 2001;Elmes et al, 2004;Stankiewicz, 2007, Nash et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The first detailed studies on the host specificity of M. teleius showed that M. scabrinodis (Nylander, 1864) was its main host species (Thomas et al, 1989) while recent studies that recorded the frequency distribution of M. teleius pupae across the host ant species have shown that its larvae can successfully develop and survive inside nests of other Myrmica species from the same site (Stankiewicz and Sielezniew, 2002;Tartally and Varga, 2008;Witek et al, 2008).…”
Section: Introductionmentioning
confidence: 99%